Global clinical trial mobilization for COVID-19: higher, faster, stronger. Issue 10 (October 2020) - Beall, Reed F.; Hollis, Aidan
Highlights: COVID-19 has prompted vastly more clinical trials than previous health emergencies. Trials started faster, are collectively larger, and are more diverse geographically. The initial trials so far are mostly not funded by industry. Lack of coordination will lead to inefficiency and duplication. Abstract : The clinical trial landscape for Coronavirus 2019 (COVID-19) is radically different from that of previous epidemics. Compared with H1N1, Ebola, and Zika, COVID-19 had an order of magnitude more clinical trials within the first 3 months following the declaration of a Public Health Emergency of International Concern (PHEIC). These trials have started much faster, are more geographically diverse, and are less likely to be funded by industry. However, the almost simultaneous design and initiation of hundreds of trials with 0.3 million participants across 78 countries creates the potential for congestion and inefficiencies and enhances risks for investors. Thus, an international coordination mechanism for clinical trials could be valuable in this and other situations.